(untitled) (Journal of KIST Medical College, 2020)
Introduction: Global pandemic of Novel corona virus (Covid 19) has become a public health emergency with multidimensional effect including education system. World has implemented physical distancing by “lockdown” strategy leading to disruption of normal routines of academic institutions. Medical students are bound to adapt web based online education system however; virtual teaching has both opportunities as well as challenges that needs to be explored for better medical education ahead. Methods: This is an observational cross sectional survey conducted on 9th batch MBBS 4th year students of KIST medical college and teaching hospital. The online survey was done by google form via emails and responses were complied on Microsoft database Excel program. Result: Out of 93 students 88 (95.44%) responded comprising 63.6% female and 36.4% male. Among them 54.5% were from within the valley whereas 45.5% were from outside the valley. 26.1% found virtual teaching was very effective with several opportunities however 58% thought online classes were slightly effective. 65.9% found 45min duration is appropriate per session. Conclusion: During the Covid pandemic, virtual online teaching has been alternative mode for continuity of medical education which can be attended from safe environment of home with proper utilization of time.